The effect of the use of indigenous knowledge-based Physics comics of Android-based marbles games on verbal representation and critical thinking abilities in Physics teaching - Almira Eka Damayanti; Heru Kuswanto (OmniaScience, 2021)
This research aims to reveal the effectiveness of the use of an indigenous knowledge-based physics comic of Android-based marbles games on verbal representation and critical thinking abilities. It is a quasi-experiment applying the pretest-posttest control group design. The research sample consists of two classes: the control and experimental classes, each of which consists of 35 students established using the cluster random sampling technique. The effectiveness of the indigenous knowledge-based physics comic of marbles games was analyzed using the quantitative method applying the effect size analysis. The result of the effect size analysis obtained from Cohen's f in verbal representation ability is 0.11 interpreted as medium effect size and critical thinking ability is 0.43 interpreted as large effect size. This shows that the developed indigenous knowledge-based physics comic of Android-based marbles games in physics teaching gives effects to verbal representation and critical thinking abilities of the students. In other words, the developed comic is effective in improving verbal representation and critical thinking abilities.